2007
DOI: 10.1007/s00216-007-1554-y
|View full text |Cite
|
Sign up to set email alerts
|

Retention behavior of ginsenosides on a poly(vinyl alcohol)-bonded stationary phase in hydrophilic interaction chromatography

Abstract: The influences of the organic component of the mobile phase and the column temperature on the retention of ginsenosides on a poly(vinyl alcohol) (PVA) bonded stationary phase operated under hydrophilic interaction chromatographic mode were investigated. The retention of the ginsenosides was found to increase with increasing amount of acetonitrile (MeCN) in the mobile phase, which is typical of hydrophilic interaction chromatographic behavior. It was also found that the retention of the analytes was highly affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…However, this linearity slightly deteriorates as the temperature of the system is decreased (R 2 values for 40, 25, 10 and 0˚C are 0.9860, 0.9825, 0.9671 and 0.9437, respectively). 49 These results indicate that hydrogen bonding is a predominant retention mechanism at elevated temperatures, and that at subambient temperatures mechanisms other than hydrogen bonding are present. Shape selectivity could be one of these mechanisms as explained by the incorporation of Ov in the MLR equations.…”
Section: Prediction By Mlrmentioning
confidence: 63%
See 1 more Smart Citation
“…However, this linearity slightly deteriorates as the temperature of the system is decreased (R 2 values for 40, 25, 10 and 0˚C are 0.9860, 0.9825, 0.9671 and 0.9437, respectively). 49 These results indicate that hydrogen bonding is a predominant retention mechanism at elevated temperatures, and that at subambient temperatures mechanisms other than hydrogen bonding are present. Shape selectivity could be one of these mechanisms as explained by the incorporation of Ov in the MLR equations.…”
Section: Prediction By Mlrmentioning
confidence: 63%
“…48 As mentioned earlier, hydrogen bonding interaction can occur between the hydroxyl groups of both the stationary phase and the analytes. In a report by our group, 49 it was found that the retention (log k) of the ginsenosides on the same chromatographic system showed a linear dependency on HBD, especially at temperatures above 25˚C. However, this linearity slightly deteriorates as the temperature of the system is decreased (R 2 values for 40, 25, 10 and 0˚C are 0.9860, 0.9825, 0.9671 and 0.9437, respectively).…”
Section: Prediction By Mlrmentioning
confidence: 99%
“…Development of novel fibrous extraction/separation media having different chemical structures and then different functionalities on the surface could be realized in the near future based on the concept of molecular shape recognition [3][4][5][6][7][8] and the systematic retention mechanism analysis with a help of various modern computational data calculations in LC [106][107][108][109][110][111][112][113][114][115][116][117][118]. Miniaturization of packed columns in GC [119][120][121][122][123] is also possible for high speed analysis with a unique selectivity but without a loss of sample loading capacity.…”
Section: Future Prospectivementioning
confidence: 99%
“…Acetonitrile, an aprotic solvent, which does not show protonedonor interactions, shows the best retention and separation selectivity among all water-miscible organic solvents in HILIC (or in ANP) chromatography. Methanol and other lower alcohols are protic solvents that provide significant hydrogen bonding interactions and compete with water for solvation of the polar adsorbent surface, decreasing the amount of adsorbed water layer on polar stationary phases (Quiming et al, 2007b). Theoretically, it is possible to substitute water by an organic solvent and to employ, e.g., a methanoleacetonitrile mobile phase in "nonaqueous HILIC chromatography," but usually the retention is weaker than that in conventional HILIC separations .…”
Section: Mobile Phase In Hydrophilic Interaction Liquid Chromatographmentioning
confidence: 99%